International law and international relations - Armstrong, J. D. [ (James David)] , 1945-; Farrell, Theo , 1967-; Lambert, Helene (Themes in international relations, 2012)
"In this fully updated and revised edition, the authors explore the evolution, nature and function of international law in world politics and situate international law in its historical and political context. They propose three interdisciplinary 'lenses' (realist, liberal and constructivist) through which to view the role of international law in world politics and suggest that the concept of an international society provides the overall context within which international legal developments occur. These theoretical perspectives offer different ways of looking at international law in terms of what it is, how it works and how it changes. Topics covered include the use of force, international crimes, human rights, international trade and the environment. The new edition also contains more material on non-western perspectives, international institutions and non-state actors and a new bibliography. Each chapter features discussion questions and guides to further reading"-- Provided by publisher